A CHANGE IN REALITY: DISCOVERING THE VALUE OF THE VIRTUAL DEMENTIA TOUR WITH FAMILY DEMENTIA CAREGIVERS. (16th November 2018) - Harrington, C; Neil, J; Roberson, D; Hardin, S; Pabbu, B
Abstract: Family dementia caregiving can be frustrating due to communication challenges. Approximately 50% of family dementia caregivers admit to some form of mistreatment of their dependent elder living with dementia. The purpose of this interpretative phenomenological study was to discover family dementia caregivers' perceptions of the Virtual Dementia Tour (VDT)®. The VDT® provided a simulation of dementia including a first person perspective of the cognitive deficits commonly seen in dementia. Participants spent eight -minutes attempting to perform common activities while experiencing sensory deprivation (poorly fitting gloves, noise producing headphones, and limited vision glasses). In-depth open semi-structured interviews were held with ten participants who were recruited from a community event offering the Virtual Dementia Tour®. The research questions were, "What are family dementia caregivers' perception of the Virtual Dementia Tour®?" and "How might the Virtual Dementia Tour® impact the family dementia caregivers' reality of the person living with dementia?" A modification of Colaizzi's (1978) method was used for interpretative phenomenological analysis. Five overarching themes emerged from the participants' language: Befuddled and Bewildered; I Just Didn't Know, Eye Opener, Doing Differently; and It Changed Me. The study findings suggest that family dementia caregivers interpreted their VDT(r) experience with empathic understanding and responsiveness. In some, this had a powerful impact with a subsequent reality change toward their family member living with dementia, which might lessen frustration and improve dyadic relational harmony and care. This study begins to fill a knowledge gap about the Virtual Dementia Tour's® value with family dementia caregivers in community settings.